2021
DOI: 10.3390/cancers13112507
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia and Tumor Immunity

Abstract: Thermal ablation is a cornerstone in the management of cancer patients. Typically, ablation procedures are performed for patients with a solitary or oligometastatic disease with the intention of eradicating all sites of the disease. Ablation has traditionally played a less prominent role for patients with a widely metastatic disease. For such patients, attempting to treat numerous sites of disease compounds potential risks without a clear clinical benefit and, as such, a compelling justification for performing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 94 publications
(111 reference statements)
1
22
0
Order By: Relevance
“…The same conclusion has been reached in previous studies on the inadequacy of the heating zone due to thermal ablation or hyperthermia for large tumors [39,84,85]. An examination of the results of the two above-mentioned methods reveals that MHT is not able to eradicate cancer cells on the edge of the tumor; additionally, conventional Dox chemotherapy has been shown to have poor drug penetration.…”
Section: Discussionsupporting
confidence: 77%
“…The same conclusion has been reached in previous studies on the inadequacy of the heating zone due to thermal ablation or hyperthermia for large tumors [39,84,85]. An examination of the results of the two above-mentioned methods reveals that MHT is not able to eradicate cancer cells on the edge of the tumor; additionally, conventional Dox chemotherapy has been shown to have poor drug penetration.…”
Section: Discussionsupporting
confidence: 77%
“…Temperature level is a challenge for hyperthermia of clinical studies, as 41.8˚C is used for wholebody temperature in humans, high temperatures such as 4245˚C strikes a problem and advanced equipment is required [26]. However, results of several studies of hyperthermia don't support the inducing of anti-tumor effects, but one research demonstrated that hyperthermia at 3941˚C for 90 min could in fact induce cellular and humoral antitumor reactions [49]. According to current clinical status, hyperthermia would damage normal brain tissue at higher temperatures (45˚C) [50].…”
Section: Discussionmentioning
confidence: 99%
“…We used heat-shocked tumor cells due to the notion that lysate of unstressed cells does not induce noticeable immune response or even can be immunosuppressive [ 33 , 34 ]. Heat shock is known to enhance antigenicity and immunogenicity by a bunch of mechanisms [ 35 , 36 ]. Here, we fractionated lysed cells and conditioned medium (see Section 4.6 ) in order to exclude crude cell mass and to ensure the absence of viable tumor cells.…”
Section: Discussionmentioning
confidence: 99%